EVANGELICAL BENCH: A PARLIAMENTARY ELITE? - Barbalho, Alexandre; Barboza, Giuliano (Faculdade de Filosofia e Ciências, 2020)
The objective of this work is to investigate whether the deputies linked to the Evangelical Bench (EB) are part of the Brazilian parliamentary elite and occupy spaces of power in the National Congress. The hypothesis is that both due to its size, as well as the media exposure that its members and their agendas reach, EB is able to impose names on the strategic positions of the Federal Chamber and participate in decision-making on the central themes of the legislative power agenda. To account for this hypothesis, it was identified whether evangelical parliamentarians 1. occupied relevant positions in the Executive Boards and Permanent Commissions and 2. were mentioned in the survey “The heads of the National Congress”. As a result, it is concluded that, despite their size and visibility, evangelical deputies, for the most part, are not part of the elite of the National Congress.